Solid Air—Low Temperature Manufacturing of Ultra-Low Permittivity Composite Materials for Future Telecommunication Systems - Nelo, Mikko; Liimatainen, Henrikki; Väätäjä, Maria; Ukkola, Jonne; Juuti, Jari; Jantunen, Heli (Frontiers in Materials, 2019)
The frequency spectrum to be used by future wireless telecommunication systems such as 5G and beyond requires novel materials which are environment-friendly, are low cost and, most importantly, have low dielectric loss and permittivity when approaching higher frequencies. In this work, the development of all-inorganic composites with a relative permittivity of ~1.2 and loss tangents in the range of 10-3 is presented. The composites were fabricated at the exceptionally low temperature of 120 °C and were based on lithium molybdate (Li2MoO4) ceramic as a water-soluble binder reinforced by quartz fibers. The relative permittivity was further decreased by the addition of hollow micron-sized glass spheres beads tekstissä esitelty sanalla sphere having very low dielectric loss. A simple manufacturing method through filtration, stencil printing and drying is presented. The microstructure of the composites was investigated with FESEM microscopy and the dielectric properties by SPDR. Printing tests were carried out in order to evaluate the possibility of using the proposed composites in, for example, printed antenna applications.